Pionowe i poziome wyrównywanie dochodów gmin - Bury, Piotr (Vertical and Horizontal Equalization of Local Government Income, 2007)
Each local government tier has been equipped with its unique set of budget income sources. Actual possibilities in gathering money by a particular local government unit depends however on many individual features, like for instance its location or kind and condition of business. The biggest differences can be met in the basic units of local government (gminas) due to their size but also to (he long list of possible revenue sources. On the other hand, all gminas have to execute the same the of public tasks, so it is vital to seem each of them with a necessary minimum of money. This is done by a system of transfers from (lie central budget, mainly in the form of a general grant (vertical equalization) which includes money from other, rich gminas (horizontal equalization). The paper shows the role of cebtral transfers in local government budgets, the general grant system for the gminas and the horizontal equalization within it.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 421-433